POTENSI PERANCANGAN WEB RESPONSIVE SEBAGAI MEDIA KOMUNIKASI VISUAL - Dewi Immaniar; Iswahyudi Iswahyudi; Wahyu Setiono (Universitas Raharja, 2016)
Currently the communication media very grown rapidly. The world was know new communication model, known as the internet. Internet is a global network that enables the establishment of communication and interaction across the globe. One very well-known form is a web-site. As the media dissemination of information through visual communication, web site is a potential and an outstanding job for visual communication designer. But sometimes a web site that has terpublis less display design principles that are executed in harmony. Rules of designing web sites less attention. Design a website in principle the same as visual communication design. Critical elements in the design of visual communication as typografi, illustration and photography are key design planning web-site display. In its design, the web is implemented using Bootstrap framework. Bootstrap itself is used as a means to create websites that can be integrated automatically when accessed on any device including PC, tablets and smartphones. In addition, the draft will be enhanced or supported by PHP, CSS, HTML, and SQL Server and design visual design with application of vector processing program and image processing program applications. Understanding of design principles and design rules are very helpful in designing web sites become more harmonious as a promotional medium of visual communication.